Peramalan KB Baru IUD dengan Metode Automatic Clustering and Fuzzy Logical Relationship - Yunidar Ayu Pratama; Diah Indriani (Universitas Airlangga, 2017)
This research aims for forecasting the number of participants Family Planning (FP) new IUD in East Java in 2017 method using Automatic Clustering And Fuzzy Logic Relationship (ACFLR). Make forecasting for the number of participants FP new IUD in the future important done. Forecasting will support the increase of the number of participants program FP new IUD as emphasized by the Government so that it can be used to take better decisions. Forecasting method of Automatic Clustering And Fuzzy Logical Relationship was chosen because the method has a higher degree of accuracy compared to the classical time series method and fuzzy time series. This study used secondary data recorded in Perwakilan BKKBN East Java in the form of the number of participants KB new IUD in East Java in 2011 to 2016. Based on the research results obtained forecasting the number of participants KB new IUD in 2017 is 65.616 participants with error rate prediction of 0.97% and the percentage increase in the number of participants from the previous year is 0.28%.